The role of motivation in EFL students' perceptions of teacher/learner responsibilities and learner abilities - Okay, Aysegul; Balcikanli, Cem (SPRINGER, 2017)
It is the aim of this study to investigate EFL (English as a Foreign Language) students' perceptions of teacher/learner responsibilities and learner decision-making abilities at tertiary level - questioning whether motivation has a role in these perceptions. To this end, 144 students who studied in the preparatory school of a state university took part in this study. In a mixed-methods research design, two questionnaires were used to collect quantitative data on students' perceptions and motivation, whereas an open-ended questionnaire was used to gather qualitative data to gain a deeper insight about the perceptions of the students. To analyze the quantitative and qualitative data, statistical analyses via SPSS Version 18 and latent level analyses were performed, respectively. The results suggested that high-motivated students do rate themselves good/very good in their decision-making abilities than their low-motivated peers. However, motivation or ability was not found to be related to students' perceptions of teacher/learner responsibilities. Since high-motivated students were good/very good at their decision-making abilities, but not more willing to share responsibilities with their teachers, it could be argued that motivation or ability alone does not ensure learner autonomy.
Keywords: Learner autonomy; Motivation; Perception; Responsibility; AUTONOMY; TEACHERS; Education & Educational Research; Linguistics